Sosialisasi Peran Pemerintah Desa Serta Partisipasi Masyarakat dalam Meningkatkan Pertumbuhan Ekonomi di Desa Kuala Bubon - Omalia, Noka; Belgiana, Chi Chi; Fadilah, Erika; Afifah, Nurul; Nurkhairan, Nurkhairan (Nawadeepa: Jurnal Pengabdian Masyarakat, 2024)
The Community Empowerment Program in the form of education is carried out in collaboration between students of the State Administration Study program and Kuala Bubon village government officials. With the theme "Community Empowerment: Socialization of the Role of Village Government and Community Participation in Increasing Economic Growth in Kuala Bubon Village" it has been successfully implemented. This socialization uses a method consisting of 3 stages, namely Pre-Socialization Activities, Socialization Activities, and Post-Socialization Activities. This socialization was attended by 25 students and 3 presenters who were Kuala Bubon Village Government Apparatuses. From the results of the socialization, it is known that Kuala Bubon Village has several village activities such as Salted Fish Processing, Kasab Embroidery, Mangrove Cultivation, and Nipah Ecotourism. In this case the village government acts as a regulator, dynamist, catalyst and facilitator. This role is supported by the participation of the Kuala Bubon village community because the opportunities, willingness and ability of the community in community empowerment have been fulfilled. Apart from that, there are also challenges faced by villages such as limited facilities, the ability of the community's technology, and seasonal changes.